Insensitive ionic bio-energetic materials derived from amino acids. Issue 1 (December 2017) - Zhang, Lei; Song, Kang-Xiang; Zhang, Zhang; Yuan, Wen-Li; Zhao, Nanrong; Qin, Song; He, Ling; Tao, Guo-Hong
Abstract Energetic salts/ionic liquids have received increasing attention as fascinating energetic materials, and the use of renewable compounds is a promising approach to developing energetic materials. Until recently, biomolecules have been used as raw materials to develop neutral energetic compounds, whereas research focused on ionic energetic materials obtained from natural bio-renewable frameworks is scarce. This work systematically investigates ionic bio-energetic materials (IBEMs) derived from sustainable natural amino acids. In addition to combustibility, high density, good thermal stability, and one-step preparation, these IBEMs demonstrated apparent hypotoxicity and insensitivity. Moreover, a theoretical examination was performed to explore their appropriate properties. The intriguing results of this study indicates that IBEMs are potential bio-based energetic materials.